The Effects of Li/Nb Ratio on the Preparation and Photocatalytic Performance of Li-Nb-O Compounds - Haifa Zhai; Hairui Liu; Hongjing Li; Liuyang Zheng; Chunjie Hu; Zhao Wang; Jingjing Qi; Jien Yang (Nanoscale Research Letters, 2017)
Abstract The effects of Li/Nb ratio on the preparation of Li-Nb-O compounds by a hydrothermal method were studied deeply. Li/Nb ratio has a great impact on the formation of LiNbO3; the ratio smaller than 3:1 is beneficial to the formation of LiNbO3, while larger than 3:1, forms no LiNbO3 at all and the morphology and chemical bond of Nb2O5 raw material are totally modified by Li ions. The reason can be attributed to the large content of LiOH, which is beneficial to form Li3NbO4 not LiNbO3, and also, even if LiNbO3 particle locally forms, it is easily dissolved in LiOH solution with strong alkalinity. Pure LiNb3O8 powders are obtained with two absolutely opposite Li/Nb ratios: 8:1 and 1:3; the former shows a unique porous and hollow structure, quite different from the particle aggregation (the latter shows). Compared with Li/Nb = 1:3, the 4.2 times higher photocatalytic performance of LiNb3O8 (Li/Nb = 8:1) are observed and it can be attributed to the unique porous and hollow structure, which provides a high density of active sites for the degradation of MB. Compared to LiNbO3, the improved photocatalytic performance of LiNb3O8 can be attributed to its layered structure type with the reduced symmetry enhancing the separation of electrons and holes.